First 10 Months of TGF Observations by ASIM. Issue 24 (19th December 2019) - Østgaard, N.; Neubert, T.; Reglero, V.; Ullaland, K.; Yang, S.; Genov, G.; Marisaldi, M.; Mezentsev, A.; Kochkin, P.; Lehtinen, N.; Sarria, D.; Qureshi, B. H.; et al.
Abstract: The Atmosphere‐Space Interactions Monitor (ASIM) was launched to the International Space Station on 2 April 2018. The ASIM payload consists of two main instruments, the Modular X‐ray and Gamma‐ray Sensor (MXGS) for imaging and spectral analysis of Terrestrial Gamma‐ray Flashes (TGFs) and the Modular Multi‐spectral Imaging Array for detection, imaging, and spectral analysis of Transient Luminous Events and lightning. ASIM is the first space mission designed for simultaneous observations of Transient Luminous Events, TGFs, and optical lightning. During the first 10 months of operation (2 June 2018 to 1 April 2019) the MXGS has observed 217 TGFs. In this paper we report several unprecedented measurements and new scientific results obtained by ASIM during this period: (1) simultaneous TGF observations by Fermi Gamma‐ray Burst Monitor and ASIM MXGS revealing the very good detection capability of ASIM MXGS and showing substructures in the TGF, (2) TGFs and Elves produced during the same lightning flash and even simultaneously have been observed, (3) first imaging of TGFs giving a unique source location, (4) strong statistical support for TGFs being produced during the upward propagation of a leader just before a large current pulse heats up the channel and emits a strong optical pulse, and (5) the t 50 duration of TGFs observed from space is shorter than previously reported. Key Points: Simultaneous measurements of TGF by two spacecraft are presented Simultaneous measurements of TGF and Elve are not rare coincidence Imaging of TGF is presented The sequence of TGF and main optical lightning pulse is resolved TGFs observed from space have shorter duration than previously reported